ANALISIS PENERAPAN SISTEM BLENDED LEARNING (STUDI KASUS DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS HKBP NOMMENSEN MEDAN) - Pasaribu, Berkat; Tobing, Artha L; Sihombing, Natalia (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to analyze the implementation of the Blended Learning system at the Faculty of Social and Political Sciences, Universitas HKBP Nommensen Medan, using a descriptive qualitative approach. Blended Learning, as a hybrid learning model combining face-to-face and online instruction, is considered an adaptive solution to the evolving dynamics of higher education, particularly in response to post-pandemic digital transformation. Data were collected through in-depth interviews with lecturers, students, and academic staff, as well as institutional documentation. The findings reveal that while Blended Learning offers flexibility and learning autonomy, its implementation still encounters significant challenges, including limited infrastructure, low digital literacy, and lack of academic interaction in online sessions. Supporting factors include the availability of digital learning materials, flexible learning schedules, and some lecturers' adaptability to technology. However, key obstacles remain, such as unstable internet connections, insufficient training for lecturers, and technological access inequality among students. This research recommends strengthening Blended Learning through regular digital literacy training, the development of user-friendly Learning Management Systems (LMS), and the provision of supportive facilities. Through a holistic approach involving all academic stakeholders, Blended Learning has the potential to evolve into an inclusive, effective, and sustainable learning model.